Evolution and dispersal of the genus Homo: A landscape approach. Issue 87 (October 2015) - Winder, Isabelle C.; Devès, Maud H.; King, Geoffrey C.P.; Bailey, Geoffrey N.; Inglis, Robyn H.; Meredith-Williams, Matthew
Abstract: The notion of the physical landscape as an arena of ecological interaction and human evolution is a powerful one, but its implementation at larger geographical and temporal scales is hampered by the challenges of reconstructing physical landscape settings in the geologically active regions where the earliest evidence is concentrated. We argue that the inherently dynamic nature of these unstable landscapes has made them important agents of biological change, creating complex topographies capable of selecting for, stimulating, obstructing or accelerating the latent and emerging properties of the human evolutionary trajectory. We use this approach, drawing on the concepts and methods of active tectonics, to develop a new perspective on the origins and dispersal of the Homo genus. We show how complex topography provides an easy evolutionary pathway to full terrestrialisation in the African context, and would have further equipped members of the genus Homo with a suite of adaptive characteristics that facilitated wide-ranging dispersal across ecological and climatic boundaries into Europe and Asia by following pathways of complex topography. We compare this hypothesis with alternative explanations for hominin dispersal, and evaluate it by mapping the distribution of topographic features at varying scales, and comparing the distribution of early Homo sites with the resulting maps and with other environmental variables.